Yield and agronomic caracteristics of soybean breeding lines in Minas Gerais State, Brazil - Hamawaki, Osvaldo Toshiyuki; Sousa, Larissa Barbosa de; Rezende, Daniela Freitas; Hamawaki, Cristiane Divina Lemes (Comunicata Scientiae, 2010)
This study evaluated yield performance of lines in the trial network of the Soybean Breeding Program of Universidade Federal de Uberlândia, in Uberaba-MG. The experiment was done at the Experimental Farm of Faculdades Associadas de Uberaba - FAZU, in the season 2007/2008, with plots consisting of four 5.0-m long rows spaced by 0.50 m. The agricultural characteristics evaluated were: plant height at flowering, plant height at maturation, insertion height of the first pod, number of days for flowering, number of days to maturity, yield and lodging, in late cycle soybean. The lines UFU-518 with 4300.3 kg ha-1 and UFU-513 with 3810.2 kg ha-1 were the most productive, with performance above the commercial controls.